‘YELLOW SYNDROME’ IN SCLERACTINIAN CORALS THROUGHOUT BINTAN DISTRICT, KEPULAUAN RIAU PROVINCE, INDONESIA - Ofri Johan; Agus Budianto (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2017)
Coral disease surveys were conducted in Bintan, Kepulauan Riau Province. The purpose was to identify the abundance of corals showing signs of Yellow Syndrome (YS) disease and to describe similar pathological signs to that of AYBD throughout Bintan District. Three belt transects (2 m x 50 m in size) were set up to determine the abundance of coral reef attacked by YS disease. Line intercept transects were used to determine the percentage of live corals in the surveyed areas. The survey showed that the YS disease syndrome attacked 8 different genera i.e. Acropora, Montipora, Porites, Pavona, Turbinaria, Favia, Platygyra, and Favites. The highest attack happened at Mapur Island (0.06 kol/m2) on Porites lutea, Turbinaria peltata, T. mesenterina, Acropora bruggemanni, and Pavona frondifera. The survey also indicated that there may have been at least two types of YS i.e. the first type caused by a boring and/or over-growing sponge species and the second type caused by a kind of pathogenic microbe. Regardless the causal agent of YS, the severity of YS attack on coral urged immediate action to be undertaken and should include initial microscopic and histology examinations. Based on this initial microscopic and histology examinations it was found out that YS bears a close resemblance to the Arabian Yellow Band Disease. This study, however, argued that the word “disease” may have been incorrectly used without identifying a specific causal agent.